Aryl Hydrocarbon Receptor–Dependent Pathways in Immune Regulation. Issue 8 (10th March 2016) - Gargaro, M.; Pirro, M.; Romani, R.; Zelante, T.; Fallarino, F.
Abstract : The idea of possible involvement of the aryl hydrocarbon receptor (AhR) in transplant tolerance can be traced back >30 years, when very low doses of dioxin—the most potent AhR ligand—were found to markedly reduce the generation of cytotoxic T lymphocytes in response to alloantigen challenge in vivo . AhR is a ligand‐activated transcription factor that is activated by dioxins and other environmental pollutants. We now know that AhR can bind a broad variety of activating ligands that are disparate in nature, including endogenous molecules and those formed in the gut from food and bacterial products. Consequently, in addition to its classical role as a toxicological signal mediator, AhR is emerging as a transcription factor involved in the regulation of both innate and adaptive immune responses in various immune cell types, including lymphocytes and antigen‐presenting cells (APCs). Allograft rejection is mostly a T cell–mediated alloimmune response initiated by the recognition of alloantigens presented by donor and recipient APCs to recipient CD4 + and CD8 + T cells. Based on those findings, AhR may function as a critical sensor of outside and inside environments, leading to changes in the immune system that may have relevance in transplantation. Abstract : Data described in this minireview identify AhR as a novel target for immunomodulation that may hold great promise in the treatment of transplant rejection and achievement of tolerance.